Desenvolvimento de produto alimentício à base de farinha de trigo integral e ingredientes funcionais - Xavier, Danniella (2013)
Lately, part of the human population has become increasingly concerned with chronic illnesses caused by poor diet, requiring changes in eating habits. The development of new food products has been enhancing the beneficial health effects by enriching substances that have proven action in preventing or reducing the risk of chronic degenerative diseases. In this study we selected the common bean, a leguminous plant that has phaseolamine as main protein and has been used by obese and diabetic patients to treat their respective illnesses. And in particular a Guava fruit with high content of carotenoids. Within this context, we selected three ingredients with functional properties: bean flour, phaseolamine and guavas microencapsulated – aiming to add to whole wheat flour, developing a food product based of enriched flour. Three different cultivars of Phaseolus vulgaris L were used to obtain a flour for each cultivar and one of them selected to develop a functional food product. In this same product, commercial powder phaseolamine and encapsulated guava pulp were added to increase nutritional value. Yield was over 98 % for all three bean flours. The chemical composition of the grains and evaluated bean flours indicated nutrient richness. To add more functional value, microencapsulated guava was obtained, concentrating certain parameters in its composition such as proteins, carbohydrates, ash, K, Na, vitamin C, phenolic compounds and total flavonoids. Lipid level decreased and total carotenoid content remained stable in microencapsulated guava, while thermal analysis indicated that decomposition of organic matter began at 160 °C. The evaluation of α-amylase activity indicated greater inhibition by the flour made from beans of cultivar Cavalo. From this flour, microencapsulated guava and phaseolamine, a new formulation named F4 was developed and selected among the others due to its superior inhibition of α-amylase activity. The enrichment showed an increase in the inhibition of amylase activity, protein content as well as total carotenoids, vitamin C and antioxidant capacity from DPPH radical. The Falling number decreased after enrichment, as well as the contents of total flavonoids and phenolic compounds. The cake (PF4) was prepared from F4. Control (C) and PF4 showed significant differences in proteins, moisture, vitamin C and total carotenoids. Microbiological analysis indicated that PF4 was fit for consumption and that tasters declared a preference for the cake (PF4). The profile of instrumental texture, color and water activity was evaluated throughout the stocking period (7 days). When subjected to clinical analysis, PF4 turned out to be viable as a glycemic index inhibitor for 80 % of volunteers non-insulin dependent who took part in the research. Thus, supplement (F4) may serve as an alternative functional and nutritional ingredient in the development of new food products, and particularly as we saw in this study for bakery products.